Anti-Leptospira spp. Antibodies in Pigs Slaughtered in the Agreste Region of Pernambuco, Brazil - Samico-Fernandes, Erika Fernanda Torres; de Albuquerque, Pedro Paulo Feitosa; Samico Fernandes, Marcela Fernanda Torres; Santos, André de Souza; Ferreira Silva, Amanda Thaís; de Queiroz Galvão, Cynthia Maria Morais; de Queiroz Rolim, Maria Betânia; Mota, Rinaldo Aparecido (Acta Scientiae Veterinariae, 2019)
Background: Swine production and productivity rates can be influenced by several factors, such as genetics, environmental conditions, nutritional factors, previous infections and others. Among infectious diseases, leptospirosis is a well-known cause of reproductive disorders in pigs. These animals are considered carriers of the disease when they are in the terminal stage of the infection and the Veterinary Inspection Service has not been notified when they are slaughtered. Considering the lack of epidemiological information on Leptospira infection in pigs in the state of Pernambuco, the aim of this study was to investigate anti-Leptospira antibodies in pigs slaughtered in the Agreste region of the state of Pernambuco, Brazil. Materials, Methods & Results: Blood samples were collected from 305 pigs in 11 municipalities in the Agreste region of Pernambuco. The animals had no history of vaccination, and were raised on subsistence-oriented family farms. The sera were subjected to the Microscopic Agglutination Test (MAT) for the detection of antibodies. The serovars used in the MAT were: Icterohaemorrhagiae, Copenhageni, Javanica, Canicola, Castellonis, Pyrogenenes, Cynopteri, Autumnalis, Sentot, Djasiman, Australis, Pomona, Grippotyphosa, Hebdomadis, Wolffi, Sejroe, Saxkoebing, Bataviae, Tarassovi, Panama, Patoc, Andamana, Celledoni, Shermani, Brastilava and Hardjo. Sera showing titers of ≥100 were considered positive. The MAT results indicated that 78/305 (25.57%) of the samples were positive, and were distributed in the 11 municipalities. The most frequent serovars were Icterohaemorrhagiae, Copenhageni, and Djasiman, with frequencies of 55.13%, 17.95% and 6.41%, respectively. Discussion: Swine infected with leptospirosis showed few or no signs of the disease. However, the bacteria can be carried for long periods in convoluted tubules of the kidney and their urinary excretion may last for years. A study of Leptospira spp. risk factors on pig farms in the state of Alagoas revealed an absence of rodent control, suggesting that this was the probable cause of infection by this serovar, Icterohaemorrhagiae. Farms that did not control their rodent populations showed a 7.8-fold higher risk of infection among their swine. This exposure poses a problem, since these animals can contaminate the environment, as well as food and water, making them an important source of infection of other animals. The findings of this study indicate that the pigs were exposed to Leptospira spp. The reason that some atypical serovars were identified in this study may be have been incidental infection, since these animals came from a non-technified system, putting them at greater risk of contact with other animal species. This may also be a reason for the identification of the other serovars in this research. Although the serovar Copenhagen is part of the Icterohaemorrhagiae serogroup, few studies have described its importance. The main reservoirs of Copenhageni are also synanthropic rodents, which underscores the importance of these animals as possible sources of contamination on farms that supply pigs to the slaughterhouses of the region under study. The data obtained here indicate the need for animal health surveillance programs in the region. Moreover, they may also be a source of infection of the professionals directly involved in handling and slaughtering pigs. This indicates the need to implement surveillance programs in the region, such as high vaccination coverage at pig farms, as well as integrated pest management against rodents.